Influence of Spindle Speed and Ratio of Variation Amplitude of Milling Process on Vibration and Surface Roughness - Tjuk Oerbandono; Mochammad Syamsul Maarif; Maverick Fadhlun Adrian Putra; Surangga Gautama; Denny Widhiyanuriyawan; Victor Yuardi Risonarta (Institute of Research and Community Outreach, Petra Christian University, 2025)
Manufacture technology by using a computer numerical control (CNC) based machine has developed rapidly, particularly in the milling process. This technology, however, still experiences challenges, one of which is chatter. To prevent chatter, several methods are used, i.e. passive, active and spindle speed variation (SSV) methods. The SSV method is easy to apply since it does not require additional tools and only uses a certain algorithm to control the spindle speed. Aluminum alloys are selected as materials for various components since it is easy to machine, corrosion resistant, lightweight, and has a high strength to weight ratio. However, series 5xxx aluminum alloys have relatively low machinability. This experimental method research using a slot milling machine aims to validate the SSV system applied to the Router 2600 Pro to Aluminum 5052 and to determine the effect of SSV modulation amplitude on the surface roughness of 5052 aluminum with RVA variations of 0 (or without SSV) to 30%. In addition, the spindle speed was also varied at 3,000; 5,000 and 9,000 rotations per minute. During the machining process, an accelerometer sensor was installed to record vibration data. The results of surface roughness measurement and vibration analysis show that the best RVA was at 20%. If the RVA increased to 30%, the vibration increased and the surface roughness worsened. Meanwhile, the best nominal spindle speeds that produce low surface roughness are 5,000 and 9,000 RPM.